1998
DOI: 10.1039/a805531i
|View full text |Cite
|
Sign up to set email alerts
|

Study of the metabolism of testosterone, nandrolone and estradiol in cattle†

Abstract: The current metabolism study was undertaken to identify key analytes in urine, plasma and bile following testosterone, nandrolone and estradiol administrations to cull cows, heifers and steers. This information will be used to develop confirmatory analysis procedures. In the present study, mixtures (1:1) of testosterone, nandrolone or estradiol and their deuterium labelled analogues were administered to cull cows, heifers and steers. Two analogues of deuterium labelled testosterone were synthesised and adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 1 publication
4
23
2
Order By: Relevance
“…4-Androsten-3,17-diol, etiocholanolone and epietiocholanolone are considered to be main metabolites of testosterone in bovine urine following administration (Samuels et al, 1998). Other possible major metabolites are 2␣-hydroxytestosterone, 6␤-hydroxytestosterone, 16␣-hydroxytestosterone, 16␤-hydroxytestosterone and estradiol (Venturelli et al, 1995;Li et al, 2002;Sanwald et al, 1995).…”
Section: Cross-reactivity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…4-Androsten-3,17-diol, etiocholanolone and epietiocholanolone are considered to be main metabolites of testosterone in bovine urine following administration (Samuels et al, 1998). Other possible major metabolites are 2␣-hydroxytestosterone, 6␤-hydroxytestosterone, 16␣-hydroxytestosterone, 16␤-hydroxytestosterone and estradiol (Venturelli et al, 1995;Li et al, 2002;Sanwald et al, 1995).…”
Section: Cross-reactivity Studymentioning
confidence: 99%
“…There are various analytical methods used for the detection of testosterone in biological fluids including, HPLC (Li et al, 2002;Navajas et al, 1995), GC-MS (Samuels et al, 1998;Saudan et al, 2004) and LC-MS offers a simplified, specific and sensitive alternative to GC-MS (Leinonen et al, 2004). Whilst these techniques have been used as quantitative and confirmatory methods, they do need expensive instrumentation, specialized personnel * Corresponding author.…”
Section: Introductionmentioning
confidence: 98%
“…The non-compliant samples were found in bovines (n = 39; 0.13 %), pigs (n = 6; 0.06 %), poultry (n = 6; 0.13 %) and aquaculture (n = 2; 0.57 %). For 26 results of anabolic steroids (80 %), Member States indicated that the source was most likely the endogenous production as reported in previous studies (Clouet et al, 1997;Samuels et al, 1998). No evidence of illegal use was found for other 5 non-compliant results for anabolic steroids.…”
Section: Hormonesmentioning
confidence: 56%
“…The non-compliant samples were found in bovines (n = 9; 0.04 %), pigs (n = 19; 0.18 %), sheep and goats (n = 4; 0.35 %) and horses (n = 3; 1.73 %). Some Member States indicated that residue findings on steroid hormones may not be attributable to illegal treatment, as the source was most likely the endogenous production as reported in previous studies (Clouet et al, 1997;Samuels et al, 1998).…”
Section: Eu Overall Assessmentmentioning
confidence: 82%